Facilitators and barriers associated with breastfeeding among mothers attending primary healthcare facilities in Mpumalanga, South Africa - Seabela, Ethel Sekori; Modjadji, Perpetua; Mokwena, Kebogile Elizabeth (Frontiers in Nutrition, 2023)
Despite the health benefits of breastfeeding for both the mother and the child, early cessation of breastfeeding remains a public health problem in South Africa, attributed to contextual barriers and facilitators. Within the context of Mpumalanga province characterised by low breastfeeding rates and high infant mortality rates in children under five years, we explored the facilitators and barriers to breastfeeding among mothers attending the three primary health facilities in Ermelo. Using a semi structured interview guide informed by the socio-ecological model, three focus group discussions and twelve in-depth interviews were conducted among purposively selected mothers. Transcripts from audiotaped and transcribed verbatim interviews were analysed through thematic analysis using NVivo version 10. Mothers were aged between 18 and 42 years and living in poor sociodemographic backgrounds. At the individual level, mothers valued breastfeeding facilitated by their commitment, maintaining it, eating healthy foods, and having sufficient breastmilk. However, returning to work, insufficient breastmilk, misconceptions on breastfeeding and interference with social life were the barriers for mothers to breastfeed continuously. At the interpersonal level, family was identified as the main form of support to breastfeeding mothers, although, family interference was also identified as a barrier. At the community level, mothers shared some family beliefs and practices, but were still split between societal and cultural norms, and traditional beliefs as facilitators or barriers to breastfeeding. At the organizational level, most mothers valued the support provided by health care workers on childcare and techniques on breastfeeding at the health facilities. They did however articulated concerns on the miscommunication some health care workers offered regarding breastfeeding, which negatively influenced their infant feeding practices. Intervention efforts should focus on behaviour change to educate and equip mothers to overcome the barriers that are within their control. Such interventions should further focus on family-centred education and strengthening the proficiency of health care workers on advising breastfeeding mothers.